국내 의료기관 수술실에서 발생한 환자안전사고의 위해정도 관련 요인 - 류민정; Minjung Ryu; 박준수; Jun Su Park; 김봄결; Bomgyeol Kim; 장석용; Suk-yong Jang; 이상규; Sang Gyu Lee; 김태현; Tae Hyun Kim (HIRA Research, 2024)
Background: Patient safety is a crucial aspect of healthcare quality and has received increased attention recently. However, safety incidents in operating rooms (ORs) remain common due to unique risk factors. Despite the higher risks in ORs compared to other departments, research on OR-specific patient safety incidents in South Korea is still limited. Methods: This study analyzed 1,131 patient safety incidents reported to the Korea Institute for Healthcare Accreditation from 2018 to 2022 to categorize incident types and frequencies in ORs, assess variations in severity based on patient, hospital, and incident characteristics, and conduct subgroup analyses by sex and hospital grade. Results: Among the 1,131 incidents, patients aged ≥80 years experienced a high frequency of sentinel events. Incidents related to infections, anesthesia/sedation, injuries, and procedures had higher adverse event rates, while burn-related incidents resulted in both adverse and sentinel outcomes. Thoracic surgeries showed a greater likelihood of sentinel events compared with general surgeries, and the incidence of sentinel events increased from 2018 to 2022. Conclusion: Factors such as patient age, incident type, surgical specialty, and year were associated with the severity of OR patient safety incidents. These findings offer valuable insights for developing preventive strategies to enhance patient safety in ORs and serve as a foundation for further research on OR-specific patient safety issues.